OPTIMAL CONTROL SYSTEM OF DIESEL AUTOMOTIVE ENGINEERING BY EXAMPLE OF OPEN PIT MOTOR TRANSPORT - Wójcik, Waldemar; Suleimenov, Batyrbek; Shadrin, Gennadiy; Shadrin, Mikhail; Porubov, Dmitriy (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper investigates the optimal control system of diesel automotive engineering with application of complex criteria, depending on fuel consumption rate and travel time, with adjustable coefficients of physical process mathematical model, considering influence of disturbing effects factors. This control principle allows saving fuel consumption rate, reducing transport influence on environment, and also reducing the importance of human factor for motor transport control.